Application and design considerations of ROS-based nanomaterials in diabetic kidney disease - Huang, Qing; Tang, Jiahao; Ding, Yunchuan; Li, Fangping (Frontiers in Endocrinology, 2024)
Diabetic nephropathy (DKD) is a common chronic complication of diabetes mellitus and an important cause of cardiovascular-related death. Oxidative stress is a key mechanism leading to diabetic nephropathy. However, the current main therapeutic approach remains combination therapy and lacks specific therapies targeting oxidative stress. With the development of nanotechnology targeting ROS, therapeutic fluids regarding their treatment of diabetic nephropathy have attracted attention. In this review, we provide a brief overview of various ROS-based nanomaterials for DKD, including ROS-scavenging nanomaterials, ROS-associated nanodelivery materials, and ROS-responsive nanomaterials. In addition, we summarize and discuss key factors that should be considered when designing ROS-based nanomaterials, such as biosafety, efficacy, targeting, and detection and monitoring of ROS.